Scientific basis of the use of salicylates in adaptive technologies of spring barley cultivation - Pashkevich, Lyubov V.; Kabashnikova, Liudmila F. (Journal of the Belarusian State University. Ecology, 2022)
The article scientifically substantiates the use of an exogenous plant metabolite, salicylic acid (SA), as an inducer of nonspecific acquired resistance in spring barley plants. Under a greenhouse experiment, a positive effect of a protective and stimulating composition based on salicylate on the parameters of growth and development of spring barley plants infected with the fungus B. sorokiniana, and the degree of their infection with a fungal disease - dark brown spotting, was revealed. Under field conditions, the stimulating effect of SA and phenyl salicylate on growth processes, the content of photosynthetic pigments in the leaf, the activity of lipid peroxidation and peroxidase in plant cells was shown. An increase in the overall resistance of spring barley plants in crops to unfavorable environmental factors, including phytopathogens, was established, which ultimately ensured the formation of a crop at the level of the standard fungicide Adexar with an increase of 4-5 centners for hectare compared to the untreated control. On the basis of the results obtained, the immunomodulatory drug “Immunakt-SA” was developed, which is a composition of SA and a water-soluble polymer VSP-3. The use of the drug ensures stable yields of barley grain at the level of standard chemical fungicides, which in the future will significantly reduce the use of expensive chemicals for plant protection and the chemical load on the environment.
Keywords: salicylic acid; immunity inducers; spring barley; dark brown spotting; photosynthetic pigments; oxidative status; stability; yield